Evolution in the Treatment of Sinonasal Inverted Papilloma: Pedicle-Oriented Endoscopic Surgery. Issue 1 (January 2014) - Pagella, Fabio; Pusateri, Alessandro; Giourgos, Georgios; Tinelli, Carmine; Matti, Elina
Background: In the literature, the global endoscopic sinus surgery (ESS) success in the treatment of sinonasal inverted papilloma (IP) is 95%. This study was designed to describe a conservative endoscopic approach, based on research of the tumor's pedicle and treatment concentrated on its site of attachment, and to compare the results of this technique with the outcome of standard endoscopic treatment. Methods: Retrospective analysis of the patients treated in our institution for paranasal inverted papilloma (IP), between 2002 and 2011 with a minimum of 18 months follow-up was performed. Group A received a standard ESS including whole sinus demucosization (maxillary, ethmoid, frontal, or sphenoid sinus) and bony wall drilling. Group B patients instead underwent pedicle-oriented endoscopic surgery (POES); in this group, bony demucosization and drilling were selectively conducted around the site of pedicle attachment of the tumor. Results: The cohort included 73 patients (median age, 60.5 years; median follow-up, 58 months). Group A/group B consisted of 37/36 patients. IP persistence—recurrence for group A/group B was 0/1 cases. Oncological success for global endoscopic/group A/group B was 98.6% (72/73)/100% (37/37)/97.2% (35/36). We noticed a significant difference in surgical operative time and postoperative complication rate among the groups, in favor of POES technique. Conclusion: Our data confirm the efficacy of the endonasal endoscopic treatment for sinonasal IP. Moreover, the even more conservative endoscopic treatment proposed (POES) seems to offer good control of the disease, shorter operating times, avoidance of unnecessary surgery with respect to uninvolved structures, and permits a follow-up aimed at the site of the pedicle attachment.